Performance of prognostic markers in the prediction of wound healing or amputation among patients with foot ulcers in diabetes: a systematic review. (January 2016) - Brownrigg, J. R. W.; Hinchliffe, R. J.; Apelqvist, J.; Boyko, E. J.; Fitridge, R.; Mills, J. L.; Reekers, J.; Shearman, C. P.; Zierler, R. E.; Schaper, N. C.; ,
Abstract: Prediction of wound healing and major amputation in patients with diabetic foot ulceration is clinically important to stratify risk and target interventions for limb salvage. No consensus exists as to which measure of peripheral artery disease (PAD) can best predict outcomes. To evaluate the prognostic utility of index PAD measures for the prediction of healing and/or major amputation among patients with active diabetic foot ulceration, two reviewers independently screened potential studies for inclusion. Two further reviewers independently extracted study data and performed an assessment of methodological quality using the Quality in Prognostic Studies instrument. Of 9476 citations reviewed, 11 studies reporting on 9 markers of PAD met the inclusion criteria. Annualized healing rates varied from 18% to 61%; corresponding major amputation rates varied from 3% to 19%. Among 10 studies, skin perfusion pressure ≥40 mmHg, toe pressure ≥30 mmHg (and ≥45 mmHg) and transcutaneous pressure of oxygen (TcPO2 ) ≥25 mmHg were associated with at least a 25% higher chance of healing. Four studies evaluated PAD measures for predicting major amputation. Ankle pressure <70 mmHg and fluorescein toe slope <18 units each increased the likelihood of major amputation by around 25%. The combined test of ankle pressure <50 mmHg or an ankle brachial index (ABI) <0.5 increased the likelihood of major amputation by approximately 40%. Among patients with diabetic foot ulceration, the measurement of skin perfusion pressures, toe pressures and TcPO2 appear to be more useful in predicting ulcer healing than ankle pressures or the ABI. Conversely, an ankle pressure of <50 mmHg or an ABI <0.5 is associated with a significant increase in the incidence of major amputation.